If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 56 = -2x + -7(-4x + 18) Reorder the terms: 56 = -2x + -7(18 + -4x) 56 = -2x + (18 * -7 + -4x * -7) 56 = -2x + (-126 + 28x) Reorder the terms: 56 = -126 + -2x + 28x Combine like terms: -2x + 28x = 26x 56 = -126 + 26x Solving 56 = -126 + 26x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26x' to each side of the equation. 56 + -26x = -126 + 26x + -26x Combine like terms: 26x + -26x = 0 56 + -26x = -126 + 0 56 + -26x = -126 Add '-56' to each side of the equation. 56 + -56 + -26x = -126 + -56 Combine like terms: 56 + -56 = 0 0 + -26x = -126 + -56 -26x = -126 + -56 Combine like terms: -126 + -56 = -182 -26x = -182 Divide each side by '-26'. x = 7 Simplifying x = 7
| 80-x=3x | | 90+90=180 | | a-12=-6 | | c-12=-7 | | c-8=2 | | 8x=180 | | 8x=90 | | 6x+3+4x-3=90 | | x-17=2x+7 | | 165=-4x-7(3x+5) | | 43-4(2+6)= | | 5x+10+2x-12=360 | | 23=3x+2y | | .33x+8=x | | 10x^2-23-42=0 | | 4x+22=180 | | b+55=21 | | 4x+22=90 | | 5x+10+2x-12=180 | | 139=59-10x | | c-5=-57 | | c-28=-14 | | 5t+52=7t+2 | | 1+8(x-9)=11-9(x-4) | | P=5m+5v | | 2y-10x=16 | | x^6-81x^4=0 | | 6x+6x+3+9=3x+5+8x | | 8x+33=48x+3 | | x-2(3-x)=2x+3(1-x) | | x+(3x+12)+90=180 | | 21x^2+8x-4=0 |